Akut ST yükselmeli miyokart infarktüsü geçiren hastalarda müracaat ve altı aylık takipte serum intermedin seviyelerinin sol ventrikül fonksiyonları ve kardiyovasküler istenmeyen olay - SEVGİLİ, Emrah (Bezmialem Vakıf University, 2014)
ABSTRACT Introduction: Intermedin (IMD) is a newly discovered peptide regulating homeostasis in cardiovascular and renal systems. It has some cardioproctective properties against hypertrophy, fibrosis and protects from atherosclerotic plaque development. The aim of this study is to measure serum IMD levels in patients with acute ST elevated myocardial infarction at hospital admission, discharge and during six month follow-up. Changes in echocardiographic measurements, major adverse cardiac events (MACE) and the association between serum IMD levels and these clinical and echocardiographical parameters are also determined. Materials and Methods: Seventy five consecutive patients (63 male, 12 female) who underwent successful primary percutaneous coronary intervention (PCI) included in the this prospective study. Demographic features and atherosclerotic risk factors of each patient were recorded. Blood samples for measurement of serum IMD levels were collected at hospital admission, discharge and during six month follow-up. Transthoracic echocardiographic (TTE) assessment was performed during inital hospitalisation in first 48 hours after revascularization procedure and at sixth month follow-up. MACE including hospitalisation due to cardiovascular reasons, re-MI, unplanned PCI, new onset heart failure and cardiovascular mortality during follow up were also recorded. Results: Most of the study patients (84%) were middle aged males (56.3 ± 9.6 years). Serum IMD levels at admission were decreased in female, hypertensive and diabetic patients (97.6 ± 19.7 pg/mL versus 139.0 ± 69.2 pg/mL, p=0.04; 109.9 ± 38.7 pg/mL versus 143.6 ± 73.3 pg/mL, p=0.03; and 103.6 ± 28.2 pg/mL versus 143.6 ± 72.5 pg/mL, p=0.02 consecutively). Also, a gradual decrease was detected in IMD levels from admission to discharge and follow-up (132.4 ± 65.6 pg/mL, 129.4 ± 73.1 pg/mL, and 119.0 ± 84.5 pg/mL consecutively). Serum IMD levels were stayed stable during follow-up in patients with decreased left ventricular end diastolic diameter (LVEDD) which was a well known marker of left ventricular dilatation and remodeling compared to markedly decreased serum IMD levels of the patients with decreased/unchanged LVEDD. MACE developed in approximately one third of patients (29 patients, 38.7%). Although serum IMD levels of the patients with MACE were lower compared to patients without MACE, the differance did not reach statistical significance (106.3 ± 30.4 pg/mL versus 126.3 ± 103.1 pg/mL, p>0.05). Re-hospitalised patients during follow-up had lower IMD (102.6 ± 20.0 pg/mL versus 141.2 ± 74.1 pg/mL, p=0.04). Conclusions: Serum IMD levels in patients with acute STEMI at hospital admission, discharge and during follow-up were closely associated with alterations of LV size and systolic functions and also MACE such as re-hospitalisation due to cardiovascular events.
Thesis (Medical)--Bezmialem Vakıf University, Faculty of Medicine, Department of Neurosurgery, Istanbul, 2014.
Keywords: Kardiyoloji = Cardiology; Kardiyoloji Anabilim Dalı; Department of Cardiology; Kalp = Heart; Kalp hastalıkları = Heart diseases; Ventriküler fonksiyon-sol = Ventricular function-left; ST segmenti = ST segment